Surgical Site Infection by Methicillin Resistant Staphylococcus aureus– on Decline? - Bhattacharya, Susmita (J Clin Diagn Res, 2016)
INTRODUCTION: Surgical Site Infection (SSI) is the most common healthcare associated infection that could be averted by antibiotics prophylaxis against the probable offending organisms. As Staphylococcus aureus has been playing a substantial role in the aetiology of SSIs, Methicillin Resistant Staphylococcus aureus (MRSA) happens to be a problem while dealing with the postoperative wound infection. AIM: To determine the prevalence of SSI caused by MRSA and the antibiotic sensitivity pattern of MRSA. MATERIALS AND METHODS: A cross-sectional study was conducted at Nil Ratan Sircar Medical College, Kolkata, West Bengal from July 2009 to December 2012. A total of 19,359 surgical procedures were done of which 3003 culture positive SSIs have been documented. The clinical samples were collected from patients of both sexes and all ages suspected to be suffering from SSI from different specialities. Samples were processed according to CLSI, 2007 guidelines. The isolated strains of Staphylococcus aureus were screened for MRSA by detection of resistance to Cefoxitin disc (zone of inhibition was ≤21 mm) and slidex staph latex agglutination tests were done on cefoxitin resistant strains to spot phenotypic expression of mec A gene. Then PCR was performed for detection of mecA gene. Antibiotic sensitivity test was done following Kirby Bauer technique. RESULTS: In this 3½ year study, 1049 Staphylococcus aureus (34.93%) were reported from 3003 cases of SSI followed by Escherichia coli (20.34%), Klebsiella spp. (18.08%), Pseudomonas spp. (7.99%), Acinetobacter spp. (7.49%) respectively. Among the Staphylococcus aureus, 267 strains were derived as MRSA (25.45%). MRSA were isolated from 167 (62.54%) male patients and 100 (37.45%) female patients having surgical site infections. Inpatients and outpatients distribution of MRSA were 235 (88.01%) and 32 (11.98%) respectively. Majority of the MRSA cases were reported from Surgery (12.49%) and Orthopaedics (11.85%) departments in the age group above 75 years (15.63%). The MRSA strains have been found to be 100% sensitive to linezolid and tigecycline followed by fucidin (92.51%), mupirocin (88.39%), levofloxacin (75.66%) and doxycycline (72.28%). No vancomycin resistant strains were detected, but 3 strains (1.12%) were found to be intermediately susceptible to it (VISA). Incidence of MRSA in SSI has been decreased by 15.17 % in 2012 in comparison to 2009. PCR revealed mecA gene was present in 96.25% of cefoxitin resistant Staphylococcus aureus strains. CONCLUSION: Staphylococcus aureus being the predominant organism causing SSIs, MRSA needs the attention for its resistance to commonly used antibiotics in the hospital like penicillin, cephalosporin group of drugs. Regular monitoring of the MRSA, involved in the SSI of a particular setup is the basic requirement to trim down the incidence of the postoperative wound infections by proper antibiotic prophylaxis.